Compositional Analyses of Mortars from the Late Antique Site of Son Peretó (Mallorca, Balearic Islands, Spain): Archaeological Implications. (11th December 2012) - Miriello, D.; Bloise, A.; Crisci, G. M.; Cau Ontiveros, M. Á.; Pecci, A.; Riera Rullan, M.
<x xml:space="preserve">Abstract</x> The paper presents the mineralogical, petrographic and chemical analyses of mortars from an Early Christian complex found in Mallorca (Balearic Islands) and dated to between the fifth and the eighth centuries ad. We characterized several mortars found at the site, in order to gather information on the raw materials used, as well as on the technology of production, and similarities among the samples. The analyses were aimed at solving specific archaeological questions regarding the building phases of the site and, in particular, the synchronic or diachronic presence of two baptismal basins in the same Christian complex.